Prediction of new potential micro RNAs-environmental factor associations based on katz measure - Vural, Huseyin; Kaya, Buket; Alhajj, Reda; Kaya, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2018)
MicroRNAs (miRNAs) have effects on regulation of gene expressions and they also have various functions on biological processes, so the disruption of functions of miRNAs can cause to diseases and abnormal phenotypes. Environmental Factors (EFs) such as drugs, radiation, cigarette smoke, alcohol have important negative effects on human health because they perform interactions at molecular level in human organisms. miRNA is one of the molecules interacting with EFs, and the interactions between them have affects on diseases. In this study, we have developed a model based on KATZ measure to find new potential associations between miRNAs and EFs with using Gaussian interaction profile kernel similarity. © 2018 IEEE.
10th IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining, ASONAM 2018 -- 28 August 2018 through 31 August 2018 -- Barcelona -- 141485
Keywords: Environmental Factors; KATZ; Link Prediction; MicroRNAs